2010
DOI: 10.1027/1016-9040/a000018
|View full text |Cite
|
Sign up to set email alerts
|

Missing or Killed

Abstract: Many people go missing during war and acts of terrorism. Do their families suffer an additional or different kind of mental health burden than families of people who are known to have been killed? Two groups of respondents, each comprising 56 women living in Bosnia and Herzegovina, were included in the study. These were women whose husbands were either confirmed as having been killed during the 1992–1995 war or who were at the time of the study officially still listed as missing as a result of the war. These t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…There is, however, inconclusive evidence whether relatives of individuals who have disappeared experience more severe mental health consequences than bereaved individuals do (e.g. [28, 29, 30]). Whether the type of loss (deceased vs. disappeared) has an impact on class membership will be explored further on.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, inconclusive evidence whether relatives of individuals who have disappeared experience more severe mental health consequences than bereaved individuals do (e.g. [28, 29, 30]). Whether the type of loss (deceased vs. disappeared) has an impact on class membership will be explored further on.…”
Section: Introductionmentioning
confidence: 99%
“…A study compared the prevalence of post-traumatic stress disorder (PTSD) in wives of missing individuals with unconfirmed death and confirmed death in Bosnia and Herzegovina. This study showed greater PTSD among wives who did not have an opportunity to see the mortal remains of their husbands (Powell et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ambiguous loss is often experienced by the friends and families of missing persons and is characterized by a lack of closure or understanding [32]. The lack of finality associated with ambiguous loss, and the added pain of “not knowing”, means that the grief related to missing persons can be longer lasting, and in some cases even more traumatic than bereavement following death [33,34]. It is therefore likely that the emotional impact of a dog going missing is at least as significant as the emotional impact of companion animal bereavement.…”
Section: How Can the Theft Of A Dog Impact Their Guardian?mentioning
confidence: 99%